An Organizational Sociology of Education: Using Structural, Network, and Ecological Perspectives to Study Schools - Trinidad, Jose Eos R (Archīum Ateneo, 2023)
Highlighting changes in education and organizational theorizing since the 1950s, this review integrates three perspectives for an organizational sociology of education. The structural perspective focuses on how the formal organization of resources, relationships, and information can influence student outcomes and inequalities through opportunities to learn. The network perspective highlights the role of informal interactions and interpretation as well as social and cultural capital to bring about changes. The ecological perspective illustrates how schools are affected by other schools (horizontal dimension), the educational bureaucracy (vertical dimension), and organizations outside schools (community dimension). An organizational perspective can concretize often abstract sociological topics on stratification, social reproduction, and socialization. The perspective can also reconceptualize often individualistic views on contemporary education issues like student well-being, teacher shortage, racial inequalities, and school politics. The review ends with a discussion on how to incorporate these organizational perspectives and how they can complement current studies in education, sociology, and public policy.